A study on the theoretical predictability of extreme value distributions for natural catastrophic events - Sabolová, Radka; Zimmermann, Pavel, 1980-; Kladívko, Kamil; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2014)
The thesis deals with natural disasters from the statistical point of view and treats them as extremal observations. Basics of classical extreme value theory will be summarized and new approach based on maximum entropy principle will be proposed. Both methods will be used in order to analyze real discharge data observed at the river Vltava.
Vedoucí práce: Pavel Zimmermann
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: statisticko-pojistné inženýrství [obor dipl. práce]; diplomové práce; master's theses